Passivity Based Control of Doubly Fed Induction Generator Using an Interval Type-2 Fuzzy Logic Controller - Izzeddine Allali; Boubekeur Dehiba (The Journal of Engineering and Exact Sciences)
The article is interested in the control of a Doubly Fed Induction Generator (DFIG) for wind energy conversion. The proposed structure is based on the association of passivity and interval type 2 fuzzy logic control. The principal objective of this task is to effectively regulate and optimize the flow of both active and reactive power from the generator to the interconnected network to ensure efficient operation and stability, with the rotor signals operated via a bidirectional converter. The proposed control technique is subjected to various conditions to evaluate its performance, including varying wind speeds and parameter adjustments. The simulation results show the robustness of the proposed control, where the integration of the interval type 2 fuzzy logic controller (IT2-FLC) enhances the dynamic performance, disturbance sensitivity, and robustness against parameter changes.